What motivated residents of Saudi Arabia to receive the COVID-19 vaccine? - Gray, Jenny; AlAnazi, Ahmed AlHumaidi; AlSumait, Fahad; Abu-Shaheen, Amani; Bashir, Muhammad Salman; Al Sheef, Mohammed (Frontiers in Public Health, 2023)
Background: Individual acceptance of vaccination is a multifactorial issue. The unprecedented speed at which COVID-19 has spread globally has meant that people had to come to terms with the idea of novel vaccines for a novel disease. Purpose: We wanted to understand the motivating factors for people living in Saudi Arabia with regard to accepting the COVID-19 vaccine, surveyed at a time when the government had mandated vaccination in order for all in order to enter public spaces (except those who are medically exempt). Methods: This is a cross-sectional survey of 802 participants currently living in Saudi Arabia. The questionnaire was distributed in a hospital in Saudi Arabia and via electronic means to the general population. Results: A total of 521 (65%) of the respondents were women, and 281 (35%) were men. A total of 710 (88.5%) were Saudi, and 55 (6.9%) were non-Saudi. The majority of participants (496, 65.7%) stated that they registered from the vaccine as soon as it was available, with 185 (24.5%) stating that they registered when they were mandated to do so and 74 (9.8%) registered only when they felt cases were increasing. Most participants (316, 41%) stated that the main reason for taking the vaccine was one of a self-protective nature, followed by indirect vaccination (240, 31.1%), paternalistic reasons (157, 20.4%) and altruistic reasons (58, 7.5%). Conclusions: With the increased burden on healthcare that is being faced by COVID-19, other resources need to be carefully allocated. This paper may aid the Saudi government in understanding the motivation for the population to take the vaccine and therefore facilitate any future vaccination campaigns to ensure the best utilization of resources.